Penerapan Rapidminer Pada Data Mining Klastering (Kasus: Distribusi Persentase Rumah Tangga Menurut Kabupaten/Kota Dan Bahan Bakar Untuk Memasak) - Ismi Azhami; Rahmi Fauziah (LPPM STIKOM Tunas Bangsa, 2020)
Fuel is any material that can be converted into energy. For example in daily life humans often use energy sources as fuel for cooking including Gas/LPG, Electricity, Kerosene, Charcoal/Briquettes, Wood and others. The purpose of this study is to classify the distribution of the percentage of fuel used in each district/city in Northern Sumatra. This study discusses the analysis of the K-Means method in the case of the distribution of household percentages by district/city and cooking fuel in North Sumatra through the North Sumatra Central Statistics Agency website. The data is processed into 2 clusters namely high level (C1) and low-level clusters (C2). Thus obtained from 34 districts/cities in North Sumatra 23 regions are grouped in high-level clusters (C1) and 10 regions are grouped in low-level clusters (C2).This needs to be done so that it becomes input in the form of information to the government to find out villages that still have low understanding and have not been fulfilled in a district/city in the Province of North Sumatra.